CHARACTERISTIC OF SOFTWARE TOOLS EXELEARNING FOR THE DEVELOPMENT OF ELECTRONIC TEXTBOOKS - Stepura, Ivan S. (Educological discourse, 2014)
Web technology is an effective educational tool, as give the opportunity not only to present course material in a convenient way, but also provides the possibility of direct interaction between student and teacher. The work provides an overview of free XHTML-editor for developing e-learning materials «eXeLearning». The study presents the main features and functionality of the system, described the experience of its use and the conclusions regarding the usefulness of the program in terms of modern national education.